2014
DOI: 10.1074/jbc.m114.551424
|View full text |Cite
|
Sign up to set email alerts
|

Corin Mutations K317E and S472G from Preeclamptic Patients Alert Zymogen Activation and Cell Surface Targeting

Abstract: Background: Corin is a protease that acts in the pregnant uterus to prevent pregnancy-induced hypertension. Results: Corin mutations K317E and S472G from preeclamptic patients impaired corin zymogen activation and intracellular trafficking, respectively. Conclusion: Mutations in the CORIN gene may impair corin function by different mechanisms. Significance: Genetic variants and mutations disrupting corin function may contribute to pregnancy-induced hypertension in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

8
2

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…Hepsin and TMPRSS3 are important for normal hearing1617. Defects in these TTSPs may lead to major diseases such as skin disorders1819, congenital or inflammatory diarrheal diseases202122, iron-deficiency anaemia232425, hypertension26272829, and hearing loss16.…”
mentioning
confidence: 99%
“…Hepsin and TMPRSS3 are important for normal hearing1617. Defects in these TTSPs may lead to major diseases such as skin disorders1819, congenital or inflammatory diarrheal diseases202122, iron-deficiency anaemia232425, hypertension26272829, and hearing loss16.…”
mentioning
confidence: 99%
“…Human corin protein was expressed with the plasmid pcDNACorin (Invitrogen) [36]. The protein encoded by this plasmid contained a C-terminal V5 tag for detection in Western blotting using an anti-V5 antibody (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…In Corin and Nppa knockout mice, uterine spiral artery remodeling was impaired, causing gestational hypertension and proteinuria (Armstrong et al, 2013; Cui et al, 2012). In humans, CORIN variants associated with preeclampsia were reported in a Caucasian population (Stepanian et al, 2014) and CORIN mutations reducing corin activity were identified in preeclamptic patients (Cui et al, 2012; Dong et al, 2014). Consistent with these findings, low levels of plasma corin were associated with the risk of preeclampsia (Khalil et al, 2015).…”
Section: Biological Functions Of Anpmentioning
confidence: 99%